Double Aortic Arch Presenting in an Adult with Dysphagia. Issue 6 (5th June 2013) - Jonker, I. De Villiers; Nunes, Abraham J.; Elhenawy, Abdelsalam M.; Das, Debraj; MacArthur, Roderick
ABSTRACT Double aortic arch is a congenital anomaly that rarely presents in adults. We describe the case of a 69‐year‐old male who presented with a double aortic arch, right arch dominant, left arch patent, experiencing progressive dysphagia since childhood. doi: 10.1111/jocs.12120 (J Card Surg 2013;28:670–672)